Interpeduncular Heterotopia and Brain Stem Cleft: An Isolated Finding Not Associated with Joubert Syndrome - Sahap, Seda Kaynak; Ucan, Berna; Keskin, Derya Bako; Goktas, Ozben Akinci; Fitoz, Suat (Neuropediatrics, 2020)
Interpeduncular heterotopia is a new neuroimaging finding reported in association with Joubert syndrome (JS) in a few cases in the literature. Nodular interpeduncular tissue was termed as interpeduncular heterotopia and anterior mesencephalic cap dysplasia in the literature in relation to gray and white matter content. We described the imaging findings and diffusion tensor imaging data of a case with interpeduncular heterotopia and brain stem cleft. This is the first case, in which interpeduncular heterotopia was an isolated finding not associated with JS.
Keywords: interpeduncular heterotopia; Joubert syndrome; diffusion tensor imaging